Transformasi Pendidikan Karakter Melalui Integrasi Sastra Anak Dalam Kurikulum Sekolah Dasar - Nurtija Alimun; Anggi Wisnawati; Harianto Adi (Jurnal Sultra Elementary School, 2023)
The current challenges of character building include moral and ethical crises due to technological advances, as well as gaps in values and labor market needs. The transformation of character education is important in realizing Indonesia's vision towards the Golden Generation 2045. This study aims to identify character education policies implemented by the Indonesian government, analyze the factors that influence the effectiveness of these policies, and analyze the roles of educational institutions, communities, and government in supporting the implementation of character education policies. Character education is one of the important focuses in the world of education in Indonesia, especially at the elementary school level. One way to integrate character education into the elementary school curriculum is through the use of children's literature. Children's literature not only functions as a medium for entertainment and language education, but can also be an effective tool for instilling character values such as honesty, courage, cooperation, and responsibility. This study aims to explore how children's literature can be used to develop character education in elementary schools and how the curriculum can be integrated to achieve these goals. Through a qualitative analysis of the use of children's literature in the elementary school curriculum, this study shows that children's literature has great potential to develop positive student character and in accordance with Pancasila values.